Aladdin songs from the motion picture soundtrack - Menken, Alan 1949- (Hal Leonard, 2019)
The soundtrack to this new 2019 live action Disney film, adapted from the original animated movie, features new lyrics by Benj Pasek and Justin Paul. Includes 6 pages of full color artwork from the film
For voice and piano, with chord symbols and guitar chord diagrams
Individual songs copyright 1992 or 2019 by Wonderland Music Company, Inc. and Walt Disney Music Company
Keywords: Motion picture music / Excerpts / Vocal scores with piano; excerpts; Vocal scores; Motion picture music; Excerpts; Popular music; Scores; Songs; Musique de film; Extraits; Partitions de chant; Musique populaire